Влияние концентрации раствора иодида калия и мощности ультразвука на кинетику окисления ионов I– в условиях кавитации - С. Д. Арсентьев (ՀՀ ԳԱԱ հրատ.)
Изучено влияние концентрации раствора иодида калия на закономерности выделения иода при воздействии ультразвуковых колебаний частотой 22 кГц в условиях кавитации. Установлено, что зависимость скорости накопления иода от концентрации KI наблюдается только при [KI] < 2%. Обнаружено существенное влияние интенсивности ультразвука на скорость выделения иода. Ուսումնասիրվել է կալիումի յոդիդի լուծույթի կոնցենտրացիայի և ուլտրաձայնի հզորության ազդեցությունը յոդի անջատման օրինաչափությունների վրա, 22 կՀց հաճախականությամբ ուլտրաձայնային տատանումների ազդեցության դեպքում, կավիտացիայի պայմաններում: Բացահայտվել է, որ յոդի կուտակման պրոցեսը ընթանում է տատանողական ռեժիմում, իսկ նրա կինետիկական բնութագիրը [KI] = 5 -15% սահմանում КI-ի կոնցենտրացիայից կախված շե: Յոդի կուտակման արագության կախումը КI-ի կոնցենտրացիայից դիտվում է միայն [KI] < 2% -ի դեպքում: Հայտնաբերվել է ուլտրաձայնի ինտենսիվության զգալի ազդեցություն յոդի առաջացման արագության վրա: The effect of KI concentration and cavitation intensity on the molecular iodine formation during the conversion of KI dissolved in water under the effect of ultrasonic vibration has been studied. Experiments were carried out in a quartz cell with water-cooling. In order to estimate the intensity of ultrasonic vibration the amplitude of displacement of the tip of wave conductor was measured. To determine iodine concentration the process was stopped at the certain time and a part of reacting mixture was removed for photocolorimetric analysis. It was shown that when the intensity of vibration at frequency 22 kHz provides the appearance of the cavitation then the transformation of KI is observed. At this the oxidation of I– takes place and molecular iodine is formed. It was found out that formation of iodine might occur in oscillatory mode. Under studied conditions the rate of iodine formation was found not to depend on initial reagent concentration if [KI]=5-15%. The decrease of initial reagent concentration in the range [KI]  2% results in deceleration of iodine formation rate. At this the increase of cavitation intensity raises the rate of iodine formation and its maximal concentration reached in the process.
Keywords: Physical Chemistry